2018
DOI: 10.1021/acscatal.8b02338
|View full text |Cite
|
Sign up to set email alerts
|

Cobaltocene Reduction of Cu and Ag Salts and Catalytic Behavior of the Nanoparticles Formed

Abstract: The modes of generation of nanoparticles (NPs) are of great interest for multiple applications in catalysis, optics, sensing, and nanomedicine. Here, fast reduction of CuSO4·5H2O and Ag salts by commercial cobaltocene yields small, stable, water-soluble Cu and Ag NPs with a narrow size distribution without any other ligand or support. The variation of the Ag salt counteranion (NO3 –, F–, BF4 –) strongly influences both the plasmonic absorption of the AgNPs synthesized in this way and the high apparent rate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 65 publications
3
17
0
Order By: Relevance
“…1 H NMR (400 MHz, CDCl 3 ) δ 7.79 (d, J = 7.6 Hz, 2H), 7.67 (s, 1H), 7.40–7.34 (m, 5H), 7.31–7.28 (m, 3H), 5.54 (s, 2H). These spectroscopic data are in accord with the literature …”
Section: Methodssupporting
confidence: 92%
“…1 H NMR (400 MHz, CDCl 3 ) δ 7.79 (d, J = 7.6 Hz, 2H), 7.67 (s, 1H), 7.40–7.34 (m, 5H), 7.31–7.28 (m, 3H), 5.54 (s, 2H). These spectroscopic data are in accord with the literature …”
Section: Methodssupporting
confidence: 92%
“…This indicated that the plasmon band of the AgNPs was sensitive to the counter anion coordinated to the AgNP surface. 27 Thus the anions Clare weak L (2-electron) ligands for such M 0 NP surfaces ( Fig. 3).…”
Section: Resultsmentioning
confidence: 97%
“…It is likely that the formation of these RhNP nanocrystals results from supramolecular electrostatic assembly involving interaction between the polyanionic RhNPs via the cobalticinium linkers. The RhNPs are compared to other MNPs 26,27 using their catalytic efficiency in the reduction by NaBH4 of the pollutant 4-nitrophenol (4-NP) to the dye 4-aminophenol (4-AP). See SI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This broad interest is due to the rich Fc chemistry and reversible redox properties at mild potential that lead to functional applications of sophisticated architectures . Substituted cobalticenium salts have distinct basic chemical properties from those of ferrocene due to the charge difference and also allow easy incorporation into polymers via carbonyl chloride or ethynyl side groups . On the other hand, permethylated ring sandwich complexes such as 1,2,3,4,5‐pentamethylferrocenyl (Fc*) and cationic organoiron complex [Fe(η 5 ‐C 5 H 4 ‐)(η 6 ‐C 6 Me 6 )][PF 6 ] (FbX) have seldom been incorporated into organic polymeric frameworks owing to the challenge in their synthesis, although Abd‐El‐Aziz has already thoroughly investigated metallomacromolecules containing [Fe(η 5 ‐C 5 H 5 )(η 6 ‐arene)][PF 6 ] units with p ‐substituted arenes.…”
Section: Introductionmentioning
confidence: 99%